Pengaruh pemberian Azolla (Azolla microphyla, Kaulfuss) dan mikroorganisme efektif terhadap produksi rumput raja (Pennisetum purpureum, Schumacher & Thonn) c.v King (Faculty of Animal Science, Universitas Brawijaya, 2013)
The research aims at determining the influence of azolla compost and effective microorganism (EM) application on the production of King Grass at the 1st and the 2nd cuttings at Sumbersekar field laboratory, Faculty of Animal Husbandry Brawijaya University for four months. The Randomized Block Factorial design was applied with two factors. The first factor was EM4 consists of E1 (EM4 addition) and E0 (without EM4). The second factor was the dosage of fertilizer consists of A100 (100% azolla + 0% urea), A75 (75% azolla + 25% urea), A50 (50% azolla + 50% urea), A25 (25% azolla + 75% urea) and A0 (0% azolla + 100% urea). The parameters observed comprised the number of tillers, plant height, dry matter (DM) leaf production, organic matter (OM) content, crude protein (CP) content. The study indicates that there were interaction (P<0.05) between EM4 and fertilizer (azolla) dosage on plant height, total OM, total CP, DM leaf production, DM stem production, total DM production, and total CP production at the first cutting. Then, at the second cutting there were interaction (P<0.05) among treatments on the number of tillers, total OM, total CP, DM leaf pro-duction, total DM production, and total CP. At the first cutting, the highest values of plant height, leaf OM, stem OM, leaf CP, stem CP, OM production were 86.39%, 92.40%, 7.85%, and 3.89% respectively found at ElA25. Furthermore, at the second cutting the best treatment were ElA25 in which the value of leaf CP content and total DM content were 8.08% and 4.64 kg/plot respectively. The leaf DM production and stem OM content at the first cutting were higher than those at the second cutting. It can be concluded that azolla can substitute the role of urea by 25%.